2006
DOI: 10.1073/pnas.0511313103
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene disruption of methionine aminopeptidase 2 results in an embryonic gastrulation defect and endothelial cell growth arrest

Abstract: The antiangiogenic agent fumagillin (Fg) and its analog TNP-470 bind to intracellular metalloprotease methionine aminopeptidase-2 (MetAP-2) and inhibit endothelial cell growth in a p53-dependent manner. To confirm the role of MetAP-2 in endothelial cell proliferation and to validate it as a physiological target for the Fg class of antiangiogenic agents, we have generated a conditional MetAP-2 knockout mouse. Ubiquitous deletion of the MetAP-2 gene (MAP2) resulted in an early gastrulation defect, which is bypas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 46 publications
4
47
0
Order By: Relevance
“…If it is not the case, this further supports the fact that MetAP2, the enzyme in charge of this cleavage, is more limiting in humans than in plants (71). This could explain why it is possible to inactivate this enzyme in plants and not in animals (72,73). Of note, these polypeptides retaining the first Met, although they do have a Thr or a Val at position 2, were found to be NAAed on the Met residue that does not correspond to a clear Nat target (14).…”
Section: N-terminalmentioning
confidence: 49%
“…If it is not the case, this further supports the fact that MetAP2, the enzyme in charge of this cleavage, is more limiting in humans than in plants (71). This could explain why it is possible to inactivate this enzyme in plants and not in animals (72,73). Of note, these polypeptides retaining the first Met, although they do have a Thr or a Val at position 2, were found to be NAAed on the Met residue that does not correspond to a clear Nat target (14).…”
Section: N-terminalmentioning
confidence: 49%
“…Antisense and siRNA also have been used to examine the role of MetAP2. Knockdown of MetAP2 results in cell growth inhibition and apoptosis in endothelial and tumor cells (13)(14)(15). The antiproliferative phenotype of MetAP2 knockdown can be recapitulated by the inhibition of the enzymatic activity of MetAP2.…”
mentioning
confidence: 99%
“…That MetAP2 is a bifunctional protein complicates the study of its function with deletion or siRNA techniques, because the eIF-2␣ has an important role in controlling protein synthesis and cell growth (8). Recently, it has been reported that MetAP2 knockout mouse embryos fail to undergo gastrulation, and targeted knockout of MetAP2 in the hemangioblast lineage caused abnormal vascular development and a lethal phenotype at the midsomite stage (13). These results clearly demonstrate an essential role of MetAP2 in embryonic development and vasculogenesis.…”
mentioning
confidence: 99%
“…Inhibitors of methionine aminopetidase 2 (MetAP2), originally developed as anti-angiogenic agents for the treatment of cancer (9), are a novel mechanism for inducing significant and sustained weight loss in animal models of obesity at low doses that do not impact angiogenesis (10)(11)(12)(13). Fumagillin, a natural product isolated from aspergillus fumigatus, is a potent and selective MetAP2 inhibitor (14).…”
Section: Introductionmentioning
confidence: 99%